Surviving the game [videorecording (DVD)] - Copeland, Stewart (New Line Home Video, 1994)
Ice-T is Mason, a homeless man recruited by a band of wealthy hunters to lead an expedition into the Pacific Northwest. But on the first day of the hunt, he discovers a lethal surprise ... he's the prey.